BANK CREDIT AND NIGERIA’S ECONOMIC GROWTH - DR. Oji Greatness Udo; Dr Anwuri; Patience N (Scholar Express Journals, 2021)
This paper investigates the significance of banks credit in stimulating output (GDP) and the factors that prompt financial intermediation within the economy. It is a contribution to the existing literature on finance and growth applied to the Nigerian economy. Evidence from this work shows that the marginal productivity coefficient of bank credit to the domestic economy (proxies by credit to the private sector) is positive but insignificant. The implication is that bank’s credit did not affect the productive sectors sufficiently for the later to impact significantly on the Nigerian economy. It was also observed that real output causes financial development, but not vice versa, and that export was not significant in driving financial development; but growth in financial sector was highly dependent on foreign capital inflows. With regard to this, the paper recommends that a strong and comprehensive legal framework that will aid in monitoring the performance of credit to the private sector and recovering debts owed to banks be established, so that banks will show willingness to lend to the private sector of the economy.
Keywords: Economic growth; Financial intermediation; Causality; Financial sector